Des féministes qui ne sont pas féministes ? - Audrey Lasserre (Glad!)
Drawing from research in literary history dedicated to the Women's Liberation Movement in France, this contribution tells a story that is specific to radical women writers in France at this time: the story of their refusal, for some in the early 1970s, for others at the turn of the 1980s, to designate themselves as feminists. This refusal is mapped out differently for the writers close to Psychoanalysis and Politics, whose project it was to "deconstruct feminism as an ideology and to bring out a female subject", and for the materialist writers who sought to deconstruct “woman” as an ideology and to bring out a subject rid of the feminine. The range of their positions—as the term “feminist” and what it supposedly refers to elicits more and more rejection over the years—reveals how much is at stake for the history of feminism as well as literary history. This overview both illustrates the goals of radical feminism and gives a better understanding of the ways in which women writers propose to transform the world and “change the life”.